Interference Mitigation Based on Low Complexity Subspace Tracking Method for Vehicle Positioning - Ping Zhang; Qiang Wu; Binbin Jing (Discrete Dynamics in Nature and Society)
Advanced driver assistance systems and automatic driving have drawn lots of attentions due to user’s multiapplication needs. Among different technologies, the integration of Inertial Navigation System (INS) and Global Navigation Satellite System (GNSS) is a key technique with the decreasing costs of Inertial Measurement Unit (IMU) and the increasing deployment of GNSS for navigation applications. Although the integration may have immune ability to interference in a certain extent, interference suppression strategy applied on the integration system can greatly improve the performance. A complete framework including interference monitor, detection, and mitigation is provided jointly using subspace tracking method and Kalman filter measurements innovation of INS and GNSS. The proposed monitor is simple, efficient, and can decide when to start the interference mitigation procedure, which can reduce the computation complexity significantly; Subspace-based method is introduced to track the interference basis matrix that can be feed to RootMUSIC to detect the frequency of interference, followed by the interference mitigation with a notch filter. The proposed framework has superior performance than the well-known time-frequency algorithm, such as short-time Fourier transform (STFT) and smoothed pseudo Wigner-Ville distribution (SPWVD), and can improve the performance of INS/GNSS system in the presence of interference with simulation verification.